2018
DOI: 10.2147/ppa.s169354
|View full text |Cite
|
Sign up to set email alerts
|

Patient–doctor relationship and adherence to capecitabine in outpatients of a German comprehensive cancer center

Abstract: PurposeThe prescribing of oral chemotherapy agents has introduced the new challenge of ensuring patients’ adherence to therapy. Aspects of a close patient–doctor relationship are reported to be correlated with adherence to oral anticancer drugs, but data on capecitabine are scarce.Patients and methodsSixty-four outpatients with a diagnosis of cancer and prescribed capecitabine were recruited from a German Comprehensive Cancer Center. We used the Patient–Doctor Relationship Questionnaire (PDRQ-9), the Medical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“… 8 10 , 18 21 Klewitz et al 8 researched the necessary information about immunosuppressants for 440 kidney transplant patients over 15 years of age and found that 46.1% of respondents were dissatisfied with the information in the item “Potential problems” and 26.7% with the item “Action and usage”. A similar pattern of results was found in people with bipolar disorder, 22 systemic lupus erythematosus, 18 using antineoplastic agents 19 , 20 or antiretrovirals 16 and other conditions. 9 , 10 People often do not take their medications due to ignorance regarding its purposes or to lack of information, especially about potential drug-related problems, 18 , 19 as seen in the current study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“… 8 10 , 18 21 Klewitz et al 8 researched the necessary information about immunosuppressants for 440 kidney transplant patients over 15 years of age and found that 46.1% of respondents were dissatisfied with the information in the item “Potential problems” and 26.7% with the item “Action and usage”. A similar pattern of results was found in people with bipolar disorder, 22 systemic lupus erythematosus, 18 using antineoplastic agents 19 , 20 or antiretrovirals 16 and other conditions. 9 , 10 People often do not take their medications due to ignorance regarding its purposes or to lack of information, especially about potential drug-related problems, 18 , 19 as seen in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…A similar pattern of results was found in people with bipolar disorder, 22 systemic lupus erythematosus, 18 using antineoplastic agents 19 , 20 or antiretrovirals 16 and other conditions. 9 , 10 People often do not take their medications due to ignorance regarding its purposes or to lack of information, especially about potential drug-related problems, 18 , 19 as seen in the current study. The perception of professionals about the quality of the information they provide is often at variance with the perception of patients or their caregivers.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[5]): more importantly appear to be determinants that are part of the Extended Common Sense Model, i.e. illness perceptions, medication beliefs, coping and more or less stable personality characteristics such as anxiety and depression [24,25,29,31,32,35,38,39]. Earlier, more or less comparable reviews published similar results (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…18 Considering the particular dose scheme of capecitabine, the clinician's actions are of fundamental importance for patients to fully understand the correct methods of administration and, regardless of possible side effects and disease progression, to maintain high adherence levels over time. 19 Concerning the importance of the doctor-patient relationship, the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) emphasizes the patient centrality, in defining adherence to treatment, since patients are found to maintain adherence to treatment when adequately informed by the prescribing clinician. 20,21 Depending on the methods used to calculate adherence, previous studies reported compliance rates for capecitabine therapy ranging from 67.9% to 98%.…”
Section: Introductionmentioning
confidence: 99%